1990
DOI: 10.1002/app.1990.070410327
|View full text |Cite
|
Sign up to set email alerts
|

Measurement method and apparatus for monitoring the kinetics of polymerization and crosslinking reactions by microwave dielectrometry

Abstract: SynopsisThe experimental apparatus employed for monitoring fast polymerizing and crosslinking processes is described in detail. The measurement method for the particular application is widely discussed and the resulting performances of the measurement technique are reported. As an example, the experimental results for polymerization and crosslinking reactions of n-butyl acrylate and 1,6-hexandiol-diacrylate are shown and the accuracy of the data acquisition is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The time evolution of the curing process was followed for 600 s irradiation time at l b 400 nm by microwave dielectrometry at 9.5 GHz, by measuring the imaginary part of the dielectric constant e'' (loss factor) of the reacting system [28]. Method and apparatus are described in detail elsewhere [29].…”
mentioning
confidence: 99%
“…The time evolution of the curing process was followed for 600 s irradiation time at l b 400 nm by microwave dielectrometry at 9.5 GHz, by measuring the imaginary part of the dielectric constant e'' (loss factor) of the reacting system [28]. Method and apparatus are described in detail elsewhere [29].…”
mentioning
confidence: 99%
“…Works on DS of free radical polymerization are rare. Rolla et al carried out microwave studies of n-butyl acrylate polymerization and photopolymerization by DS [20,21]. The mechanisms of epoxy and radical polymerizations are completely different.…”
Section: Introductionmentioning
confidence: 97%
“…A few studies on conductivity and dielectric properties have been reported for monitoring direct emulsion polymerization using conductivity data to monitor particle nucleation and particle number . Dielectric constant variation has been used for conversion monitoring in solution polymerization of n ‐butyl acrylate and methyl methacrylaylate and in solution copolymerization of n ‐butyl acrylate and methyl methacrylaylate …”
Section: Introductionmentioning
confidence: 99%
“…A few studies on conductivity and dielectric properties have been reported for monitoring direct emulsion polymerization using conductivity data to monitor particle nucleation 27 -29 and particle number. 30 -32 Dielectric constant variation has been used for conversion monitoring in solution polymerization of n-butyl acrylate 33 and methyl methacrylaylate 34 and in solution copolymerization of n-butyl acrylate and methyl methacrylaylate. 24 To the best of our knowledge there is no report on the monitoring of IEP using electrical impedance spectroscopy (EIS), a versatile tool which provides conductance and capacitance over a range of frequencies.…”
Section: Introductionmentioning
confidence: 99%